A Latina Developer Confronts Implicit Bias in CTL Hiring. (12th June 2019) - Artze‐Vega, Isis
Abstract: This chapter describes the author's experience of applying for a Center for Teaching and Learning (CTL) Directorship during which personal, institutional, and educational development identities intersected. Recommendations for inclusive CTL searches are provided.